PENGARUH PEMBERIAN DOSIS PROBIOTIK YANG BERBEDA PADAPAKAN KOMERSIL TERHADAP PERTUMBUHAN IKAN LELE DUMBO(Clariasgariepinus) PEMELIHARAAN PADAT TEBAR TINGGI - Setiawan Eka Putra; Endah Sri Redjeki; Sa’idah Luthfiyah (Universitas Muhammadiyah Gresik, 2018)
African catfish (Clarias gariepinus) is one type of freshwater fish that has high economic value. African catfish with intensive cultivation are hampered by the high cost of feed that is not in accordance with the selling price of African catfish. An alternative effort that can be done is the addition of probiotics to feed which is expected to reduce feed costs. Probiotics are living microorganisms in fish culture that can prevent disease, thereby increasing production and can reduce economic losses. This study aims to analyze the effect of probiotics on the growth of absolute weight and daily growth rate of African catfish. The method used was Completely Randomized Design (RAL) with 4 treatments namely 0, 2, 4 and 6 ml / kg of feed and repeated 3 times. Activities carried out in this study include preparation of containers, seed stocking, fish sampling, feed preparation, feeding and water management. The variables observed were absolute weight growth and daily growth rate. The results showed that the addition of probiotics to commercial feed significantly affected the growth of weight and daily growth rate of African catfish